Liquid State Bioconversion of Sewage Treatment Plant Sludge - Ahmadun, Fakhru'l-Razi (2010)
A Liquid State Bioconversion (LSB) process for treating STP sludge having the steps of providing sludge at a desired rate, mixing the sludge with mixed fungi, adding carbohydrate as nutrient source into the mixture and controlling the mixed fungi activity in the mixture in a batch fermenter under suitable condition to enchance the biodegradation, bioseparation and biosolid accumulation of the sludge, whereby the biosolids ca be used as pretreated material for rapid composting in Solid State Bioconversion (SSB) process and the biodegraded sludge supernatant can be disposed without any further treatement.